Bile Salts Stimulate Recruitment of IpaB to the Shigella flexneri Surface, Where It Colocalizes with IpaD at the Tip of the Type III Secretion Needle - Olive, Andrew J. (American Society for Microbiology, 2007)
Shigella flexneri uses its type III secretion apparatus (TTSA) to deliver invasins into human cells. This TTSA possesses an external needle with IpaD at its tip. We now show that deoxycholate promotes the stable recruitment of IpaB to the needle tip without inducing a rapid burst of type III secretion. The maintenance of IpaB at the needle tip requires a stable association of IpaD with the Shigella surface. This is the first demonstration of a translocator protein being stably associated with the TTSA needle.